Getting to global: An evolutionary perspective of brand expansion in international markets - Townsend, Janell D; Yeniyurt, Sengun; Talay, Mehmet Berk (Journal of International Business Studies, 2009)
The globalization of brands is an evolutionary process that is determined by environmental and firm-level factors, including a brand's position in the firm's global brand architecture. A framework is developed incorporating aspects of environmental uncertainty, mimetic behavior, and experiential learning as they relate to the globalization of brands. Global brand architecture is introduced as an important strategic consideration of a brand's position and stage of internationalization. The hypotheses are tested within the context of the global automotive industry, employing an event history analysis with time-varying covariates. The results reveal complex effects with respect to the role of market attractiveness, experiential learning, and mimetic behavior in globalization patterns. Overall, this study suggests that firms can accelerate the process of creating global brands if they enter the three major continents in the early stages of international expansion.